Ice‐Breaker vs. Standalone: Comparing Alternative Workflow Modes of Mid‐level Care Providers. Issue 11 (24th July 2017) - White, Denise L.; Torabi, Elham; Froehle, Craig M.
Abstract : Capitalizing on the operational concept of division‐of‐labor, clinics often reduce physician service time by off‐loading some of his/her clinical activities to lower‐cost personnel. These personnel, such as nurse practitioners and physician assistants, are often collectively referred to as "mid‐level providers" (MLPs) and can perform many patient‐consultation tasks. The common rationale is that using an MLP allows the physician to serve more patients, increase patients' access to care, and, due to MLPs' lower salaries, improve the clinic's financial performance. An MLP is typically integrated into the outpatient clinic process in one of two modes: as an "ice‐breaker, " seeing each patient before the physician, or as a "standalone" provider, a substitute for the physician for the entirety of some patients' visits. Despite both of these modes being widely used in practice, we find no research that identifies the circumstances under which either one is preferable. This study examines these two modes' effects on operational performance, such as patient flow and throughput, as well as on financial measures. Using queueing and bottleneck analysis, discrete‐event simulation, and profit modeling, we compare these two deployment modes and identify the optimal policies for deploying MLPs as either ice‐breakers or as standalone providers. Interestingly, we also find there exists a range of scenarios where not hiring an MLP at all (i.e., the physician works alone) is likely to be most profitable for the clinic. Implications for practice are discussed.